(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
In this current era of technology, industrialization and urbanization human beings have become more inclined towards unhealthy diet, sedentary lifestyle and stress which has given rise to various lifestyle related disorders of which Hypertension is of utmost significance. Considering its increasing prevalence and development of drug resistance a study related to clinical evaluation of Raktadabashamak Ghana Vati (a self formulated drug) consisting of Root of Jatamansi (Nordostachys jatamansi) - 1 part, Root of Gokshura (Tribulus terrestris) - 1 part, Stem Bark of Arjuna (Terminalia arjuna) - 1/2part, Whole herb of Brahmi (Bacopa monnireri) - 1 part. Root of Vacha (Acorus calamus) - 1/4 part, Root of Tagara (Valeriana wallichii) - 1/2 part, was undertaken in 20 hypertensive patients for 2 months. Results obtained with Raktadabashamak Ghana Vati 2 tablets twice daily after meals with luke warm water on 18 patients were 18.6% relief in Systolic Blood Pressure, 18.5% relief in Diastolic Blood Pressure, 9.3% relief in Pulse rate, 18.8% relief in Pulse pressure, 19.05% relief in Mean Arterial Pressure which were all statistically highly significant. Overall response of Raktadabashamak Ghana vati was excellent in 17.6% patients and marked improvement in 41.1%. These facts lead to the conclusion that Raktadabashamak Ghana vati can be a effective treatment for essential hypertension. Remission of treatment lead to increase in Blood pressure However, Study should be repeated by taking sample with longer duration to see whether the recurrence of disease in follow ups has decreased or not.